The Educational Effects of the Resurrection - AYAD NAEEM MAJEED ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The study dealt with the most important pillars of the religion (Resurrection), which represented the essence of what the prophets brought (peace be upon them). As for the issue of denying the Day of Resurrection, just because it is difficult to accept it or to flee from responsibility and indulge in lusts. This study discussed the universality of the issue and the proof of the existence of the enemy mentally. Because the mind is unable to comprehend the details of the Resurrection and what happens in the grave, the isthmus, and the resurrection, being outside its limits. Accordingly, the study focused on the Resurrection in the Resurrection. If the resurrection is only the soul and happiness and torment are related to it, then the resurrection will be spiritual, and if the resurrection is the body and happiness and torment are related to it, then the resurrection will be physical. Accordingly, the study proved the spiritual and physical resurrection by the rational methods used by philosophers, to show that the mind and the law do not differ in proving the existence of the resurrection and that the consolidation of this important pillar (the resurrection) in the belief of man rationally and legally will lead to many educational effects on his individual and social life, which include: A sense of responsibility in a person's relationship, dealings, behaviors, and actions with others, in addition to raising the moral level due to the frequent tendency towards moral dimensions. The human goal in the resurrection will be a light that illuminates him in the course of his life, which will lead to the consolidation of faith in the unseen, monotheism and belief in the news of prophecy, and will qualify him to acquire perfection and virtues.